Acupuncture as a primary and independent treatment for a patient with chronic insomnia: One-year follow-up case report. Issue 52 (December 2017) - Zhang, Wanrong; Huang, Zhen; Jin, Yuanyuan
Abstract: Rationale: Insomnia is a common disease. Till date, no study has reported the long-term (up to 1 year) outcomes of acupuncture as a primary and independent treatment in patients with insomnia. This report aims to present response of patient who was treated by acupuncture. This patient was evaluated with polysomnography. Patient concerns: A 40-year-old patient had been diagnosed with insomnia for 2 years and getting worse since 1 month ago. He had undergone depression and anxiety emotion, but refused to take medical treatment for chronic insomnia. Diagnoses: In this study, the diagnosis of chronic insomnia was based on the International Classification of Sleep Disorders insomnia. The patient had no obvious differential diagnosis. Interventions: Acupuncture treatment was planned for this patient who refused to take medical treatment with chronic insomnia. So the patient received 1 hour of acupuncture treatment for 12 weeks. Outcome: Polysomnographic evaluation was performed at baseline and 3 months, and 1 year after acupuncture treatment. He was asked to keep a diary of all his insomnia-related symptoms. All outcome measures substantially improved. Moreover, during the observation period, the patient's sleep quality did not worsen. Lessons: After acupuncture treatment, improvements of subjective symptoms such as unrefreshing sleep, sleep disturbances, accompanied symptoms (morning headache, fatigue, and mood worsening) were observed. Remarkable improvement was recorded by polysomnographic parameters. The costs of the treatment of insomnia may be reduced, if this therapy was proved useful in future controlled studies.